Mussel-Inspired Adhesive and Injectable Poly(oligo(ethylene glycol) methacrylate)-based Hydrogels that Promote Dermal Wound Healing and Tissue Regeneration - Randhawa, Gurpreet K (My University, 2023)
Traditional methods for dermal wound closure such as sutures and staples are invasive and can result in soft tissue trauma, increasing the likelihood of localized inflammation and infections. Alternately, while tissue adhesive alternatives can effectively seal and adhere to the wounds, they can also present safety concerns relating to immunogenic responses and tissue toxicity. Herein, we fabricate injectable, adhesive, and cytocompatible poly(oligo(ethylene glycol) methyl ether methacrylate) (POEGMA)-dopamine (DA) hydrogels co-crosslinked via hydrazone and self-polymerized dopamine crosslinks that exhibit high water retention, improved tissue adhesiveness, and effective tissue regeneration properties. POEGMA-DA hydrogels exhibit independently tunable gelation properties based on their dual crosslinking mechanism, allowing for gelation as fast as 24 s (allowing for injection and rapid filling of irregularly-shaped wounds) while achieving relevant compressive moduli of up to 37 kPa and in vitro skin adhesion strengths of up to 1.2 kPa. The POEGMA-DA hydrogels induced no significant inflammation while demonstrating high interfacial adhesiveness in a stented skin excisional mouse model, enabling efficient dermal tissue regeneration by supporting collagen remodelling and enabling the regeneration of hair follicles, sebaceous glands, and blood vessels at the excision site over the 14-day study timeline. As such, injectable POEGMA-DA hydrogels represent a relevant non-toxic and adhesive alternative wound closure system for treating deep dermal wounds.
Keywords: mussel-inspired; POEGMA; in situ hydrogels; tissue adhesive; tissue regeneration; dermal wound healing